Contributions and Challenges of the School of Libraries, Documentation and Information of the National University: period 1977-2005 - Nuñez Picado, Lilliam (2006)
The work of the librarian focuses on investigating information in its behavior, production, collection, organization, dissemination, storage, access, and retrieval for later use. For this, the author is interested in presenting what have been the main contributions of the School of Library, Documentation and Information of the National University between 19770 and 2005, poses a series of questions about the transformations that has undergone this academic unit and answers them in a way that reflects chronologically the development of the career.